1996
DOI: 10.1111/j.1365-2621.1996.tb10926.x
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of Aqueous Chlorine and Chlorine Dioxide Solutions in a Fish Model System

Abstract: A commercial ClO 2 -producing solution killed mostly Escherichia coli, Listeria monocytogenes Scott A and its streptomycin-resistant (Str R ) strain at 15, 10, and 7.5 ppm, respectively, while aqueous ClO 2 and chlorine achieved similar results against the tested strains at 20 and 25 ppm, respectively. Aqueous ClO 2 and the commercial solution were more effective than aqueous chlorine in killing Str R -L. monocytogenes inoculated on fish cubes (mangrove snapper) at 3.4 ϫ 10 3 or 2.4 ϫ 10 6 CFU/g, as well as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
4
20
0
1
Order By: Relevance
“…The rates of inactivation observed with the two compounds were similar, and in the presence of 100 mg/l of active chlorine viability decreased by 4.41 log units for both compounds, compared with less than 1.0 log unit decrease in viability that was observed when cells were submitted to 45 mg/l of active chlorine. Similar findings were reported by Lin, Huang, Cornell, Lin, and Wei, 1996, who observed that L. monocytogenes washed off the fish cubes at high-level inoculation was not completely eliminated by the three chlorinating solutions used (aqueous chlorine, chlorine dioxide obtained in situ and commercial chlorine dioxide), even at 400 ppm. Tsai, Schade, and Molineux, 1992 showed that poultry chlorinating chiller water at 40 mg/l of chlorine reduced L. monocytogenes in poultry by only 37-50% in 3-5 min.…”
Section: Inactivation Of L Monocytogenes By Chlorinating Solutionssupporting
confidence: 88%
“…The rates of inactivation observed with the two compounds were similar, and in the presence of 100 mg/l of active chlorine viability decreased by 4.41 log units for both compounds, compared with less than 1.0 log unit decrease in viability that was observed when cells were submitted to 45 mg/l of active chlorine. Similar findings were reported by Lin, Huang, Cornell, Lin, and Wei, 1996, who observed that L. monocytogenes washed off the fish cubes at high-level inoculation was not completely eliminated by the three chlorinating solutions used (aqueous chlorine, chlorine dioxide obtained in situ and commercial chlorine dioxide), even at 400 ppm. Tsai, Schade, and Molineux, 1992 showed that poultry chlorinating chiller water at 40 mg/l of chlorine reduced L. monocytogenes in poultry by only 37-50% in 3-5 min.…”
Section: Inactivation Of L Monocytogenes By Chlorinating Solutionssupporting
confidence: 88%
“…The solution with the NaOCl (OCl -) ion is a very poor disinfectant which is far less effective as a disinfectant than HOCl. In this study calcium hypochlorite is found to be more effective disinfectant in eliminating plant surface microorganisms [40]. Our results are in agreement with earlier studies on attempts using various sterilization methods [55,52].…”
Section: Discussionsupporting
confidence: 83%
“…Test organisms were incubated in lysogeny broth (LB) for 20h at 37°C until the stationery phase was reached. Antimicrobial activity of endophytic actinomycetes extract was evaluated by Disc diffusion paper-disc method with slight modification [40]. Discs impregnated with an ethyl acetate extracts, dried in laminar air flow and placed over the agar surface of plates freshly inoculated with test organisms.…”
Section: Isolation and Purification Of Endophytic Actinomycetesmentioning
confidence: 99%
“…The number of bacteria in fresh fish can be decreased and the shelf-life prolonged through washing the product using high pressure water jets or using a 0.1% chlorine-cetylpyridine solution (Mayer and Ward, 1991). Sprayed chlorine, chlorine dioxide or potassium sorbate can also be used to reduce the bacterial count in fresh fish (Mayer and Ward, 1991;Lin et al, 1996). Several methods can be used to decrease or inhibit decaying changes, such as refrigerated storage, freezing, drying, heat processing, use of additives and chemical preservatives, irradiation and packaging (Sharp et al, 1986).…”
Section: Fish Shelf-live and Deteriorationmentioning
confidence: 99%